Business process management workshops : BPM 2019 international workshops Vienna, Austria, September 1-6, 2019 : revised selected papers /: BPM 2019 international workshops Vienna, Austria, September 1-6, 2019 : revised selected papers. ([2019]) - Unknown
No abstract available